Investigation of a kinetic model reproducing the mechanisms of oligodendrocytes differentiation - Nikolov, S. G.; Nenov, M.; Vera, Julio (Series on Biomechanics, 2021)
Studying of the gene regulatory architecture that controls region-independent dynamics of oligodendrocyte differentiation, Cantone and co-authors derived a kinetic model in 14 ordinary differential equations (ODEs) [Cantone, M. Kuspert, M., Reiprich, S., et al., Glia 67(5), 825-843, 2019]. In this paper, we investigate a reduced version of this model. The reduced model consists four ODEs of mSox9, mSox10, mOlig2 and miR cluster. The cluster is composed of four microRNAs, namely miR17, miR335, miR338, and miR155. The model predicts that the morphogen gradients (signals) and the transcription rate of Olig2 mRNA play a key role in the dynamic behaviour of the model, such as stability, bistability and instability (including self-oscillations (stable limit cycle)).
CRIS-Team Scopus Importer:2021-07-30
Keywords: Analysis; Dynamical behaviour; Kinetic model; Oligodendrocytes